An atypical presentation of small bowel obstruction and perforation secondary to sporadic synchronous intra-abdominal desmoid tumours. (2016) - Abdalla, Sala; Wilkinson, Michelle; Wilsher, Mark; Uzkalnis, Aleksandras
Highlights: Intra-abdominal desmoid tumours have a poor prognosis as they can cause intestinal bleeding, obstruction and perforation. The authors report a rare case of small bowel obstruction and perforation secondary to sporadic, synchronous intra-abdominal desmoid tumours. In non-emergency presentations of desmoid tumours, it is essential to exclude hereditary polyposis syndromes. Sporadic intra-abdominal desmoid tumours should be managed in a specialist sarcoma unit. In the presence of polyposis syndromes patients with desmoid tumours should be managed at a specialist colorectal unit. Abstract: Introduction: Desmoid tumours (DTs) are rare, soft tissue tumours which account for 0.03% of all neoplasms. They are characteristically locally invasive but do not metastasize. There is frequent association with females of reproductive age, a history of abdominal surgery or trauma and a family history of fibromatoses. Intra-abdominal DTs are infrequently sporadic and more commonly associated with inherited disorders such as familial adenomatous polyposis (FAP), attenuated FAP and Gardener's syndrome. Presentation of case: The authors report a rare case of small bowel obstruction and perforation secondary to sporadic, synchronous intra-abdominal DTs in a 54-year old man with atypical symptoms and no risk factors or family history. Discussion: Intra-abdominal DTs have a worse prognosis as they can cause intestinal bleeding, obstruction and perforation. Due to the rarity of these tumours there are no clear guidelines on their management and this is instead based on small case series from specialist centres. In the non-acute setting patients with sporadic intra-abdominal DTs should be managed in a specialist sarcoma unit by a multidisciplinary team. In the presence of FAP or other polyposis syndromes patients with DTs should be managed at a specialist colorectal unit. Emergent presentations require emergency surgery in suitable candidates. Conclusion: In non-emergency presentations of DTs, it is essential to exclude FAP, AFAP and other hereditary polyposis syndromes since this affects treatment and subsequent follow-up.